The Embase UK filter: validation of a geographic search filter to retrieve research about the UK from OVID Embase. (25th March 2019) - Ayiku, Lynda; Levay, Paul; Hudson, Thomas; Craven, Jenny; Finnegan, Amy; Adams, Rachel; Barrett, Elizabeth
Abstract: Background: The authors developed a validated geographic search filter to retrieve research about the United Kingdom (UK) from OVID Embase. It was created to be used alongside their previously published OVID MEDLINE UK filter in systematic literature searches for context‐sensitive topics. Objectives: To develop a validated geographic search filter to retrieve research about the UK from OVID Embase. Methods: The Embase UK filter was translated from the MEDLINE UK filter. A gold standard set of references was generated using the relative recall method. The set contained references to publications about the UK that had informed National Institute for Health and Care Excellence (NICE) guidance and it was used to validate the filter. Recall, precision and number‐needed‐to‐read (NNR) were calculated using a case study. Results: The validated Embase UK filter demonstrated 99.8% recall against the references with UK identifiers in the gold standard set. In the case study, the Embase UK filter demonstrated 98.5% recall, 7.6% precision and a NNR of 13. Conclusion: The Embase UK filter can be used alongside the MEDLINE UK filter. The filters have the potential to save time and associated resource costs when they are used for context‐sensitive topics that require research about UK settings.